2016
DOI: 10.17137/korrae.2016.24.4.11
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation for Recycling of Organic Waste

Abstract: Depletion of natural resources and reduction of greenhouse gas emissions are an important issue which we have to solve. The recycling of waste has emerged as a global concern. In Korea, the development of cost-effective treatment and recycling technologies also need to be improved. In this study, we compared and analyzed the cost per unit of treatment and recycling of organic waste, and presented an effective recycling scheme. We investigated the current status of treatment and costs for six types of organic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies have revealed the wastewater treatment costs in CIPs, including investment, operation, and maintenance spending (Chen et al, 2013;Long et al, 2018;Nättorp et al, 2017) and costs targeting different discharge emission limits (Lyu et al, 2020). The waste gas treatment (Prado et al, 2009) and solid waste treatment (Yoo et al, 2016) costs have also been explored, and the cost related to greenhouse gas mitigation in solid waste treatment has been widely considered (Guo et al, 2020;He et al, 2013;Otoma & Diaz, 2017;Schneider et al, 2012;You et al, 2016). However, since the pollutants transfer and transform among three phases in waste treatment, the whole-process cost of end-of-pipe treatment is not a simple addition of the costs above but should clarify the relationships and boundaries of gaseous, liquid, and solid pollutants, and then cover the costs incurred in the whole process from waste generation, treatment to final discharge into the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed the wastewater treatment costs in CIPs, including investment, operation, and maintenance spending (Chen et al, 2013;Long et al, 2018;Nättorp et al, 2017) and costs targeting different discharge emission limits (Lyu et al, 2020). The waste gas treatment (Prado et al, 2009) and solid waste treatment (Yoo et al, 2016) costs have also been explored, and the cost related to greenhouse gas mitigation in solid waste treatment has been widely considered (Guo et al, 2020;He et al, 2013;Otoma & Diaz, 2017;Schneider et al, 2012;You et al, 2016). However, since the pollutants transfer and transform among three phases in waste treatment, the whole-process cost of end-of-pipe treatment is not a simple addition of the costs above but should clarify the relationships and boundaries of gaseous, liquid, and solid pollutants, and then cover the costs incurred in the whole process from waste generation, treatment to final discharge into the environment.…”
Section: Introductionmentioning
confidence: 99%